2018
DOI: 10.1002/hipo.23042
|View full text |Cite
|
Sign up to set email alerts
|

ABCA7 risk variant in healthy older African Americans is associated with a functionally isolated entorhinal cortex mediating deficient generalization of prior discrimination training

Abstract: Using high‐resolution resting state functional magnetic resonance imaging (fMRI), the present study tested the hypothesis that ABCA7 genetic risk differentially affects intra‐medial temporal lobe (MTL) functional connectivity between MTL subfields, versus internetwork connectivity of the MTL with the medial prefrontal cortex (mPFC), in nondemented older African Americans. Although the association of ABCA7 risk variants with Alzheimer's disease (AD) has been confirmed worldwide, its effect size on the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 79 publications
2
20
0
Order By: Relevance
“…Wachinger et al used MRI to study asymmetry in four pre-selected brain regions (hippocampus, amygdala, putamen, and caudate) and found significant association between rs4147929 and hippocampal asymmetry, particularly within the AD subgroup [52]. Additionally, studies with relatively smaller study populations reported associations between ABCA7 GWAS SNPs and decreased gray-matter density in dementia patients [50], increased cortical and hippocampal atrophy in controls and individuals with MCI [48], and dissociation of entorhinal cortex resting-state functional connectivity based on functional MRI in cognitively healthy elderly [51]. In summary, evidence is presently linking AD-associated ABCA7 common variants to increased brain atrophy already at preclinical stages of AD (Table 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wachinger et al used MRI to study asymmetry in four pre-selected brain regions (hippocampus, amygdala, putamen, and caudate) and found significant association between rs4147929 and hippocampal asymmetry, particularly within the AD subgroup [52]. Additionally, studies with relatively smaller study populations reported associations between ABCA7 GWAS SNPs and decreased gray-matter density in dementia patients [50], increased cortical and hippocampal atrophy in controls and individuals with MCI [48], and dissociation of entorhinal cortex resting-state functional connectivity based on functional MRI in cognitively healthy elderly [51]. In summary, evidence is presently linking AD-associated ABCA7 common variants to increased brain atrophy already at preclinical stages of AD (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, correlations between ABCA7 SNPs and clinical symptoms have been observed, yet based on relatively small cohorts, or with associations not passing multiple-testing correction. These include: association with baseline cognitive performance and linear rate of change [59], increased likelihood of clinical symptoms in individuals with AD neuropathology [60], later age at onset and shorter disease duration [53], and behavioral generalization deficits [51]. On the other hand, large-scale studies found no, or complex associations between ABCA7 sentinel SNPs and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, in our current sample of cognitively healthy older African Americans, we did not see any difference in generalization errors or performance on the standardized neuropsychological assessments between carriers of the risk vs. non-risk genotype. Furthermore, in a previous study we investigated the effect of ABCA7 rs115550680, a variant with a significantly increased risk for AD exclusively in African-Americans (Reitz et al, 2013), on the same behavioral paradigm; we found that non-demented African American elderly with the ABCA7 rs115550680 risk genotype had impairments in generalization, mediated by cortico-hippocampal network dysfunction (Sinha et al, 2018). Taken together, these results indicate that in African Americans, ABCA7 rs3764650 does not confer a direct AD risk, but rather indirectly increases the risk of AD by diminishing the benefits of aerobic fitness.…”
Section: Discussionmentioning
confidence: 97%
“…Another variant, ABCA7 rs115550680, has been linked to the development of late-onset AD in African Americans (Reitz et al, 2013). We have previously demonstrated that in non-demented African American elderly, rs115550680 corresponds to impairments in MTL network function commensurate with hippocampus-related cognitive deficits (Sinha et al, 2018). Despite ABCA7 rs3764650 not being directly implicated in AD in African Americans, we hypothesized that it may yield an indirect risk through its interaction with other risk factors, which in turn, could account for the higher incidence rate of dementia and AD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not ABCA7 knockout impacts cognitive function needs to be studied. Suggestive of an effect on synaptic function, a recent study found that healthy ABCA7 carriers show impaired cortical connectivity (Sinha et al, 2019). Interestingly, there might be genetic interactions between APOE4 with ABCA7 that impact memory (Chang et al, 2019).…”
Section: Abca7mentioning
confidence: 99%